O-GlcNAcylation in Chronic Lymphocytic Leukemia and Other Blood Cancers - Spaner, David E. (Frontiers in Immunology, 2021)
In the past decade, aberrant O-GlcNAcylation has emerged as a new hallmark of cancer. O-GlcNAcylation is a post-translational modification of serine and threonine residues in intracellular proteins that occurs when the amino-sugar β-D-N-acetylglucosamine (GlcNAc) made in the hexosamine biosynthesis pathway (HBP) is covalently attached by the glycosyltransferase O-GlcNAc transferase (OGT). O-GlcNAc moieties reflect the metabolic state of a cell and are removed by O-GlcNAcase (OGA), encoded by MGEA5. O-GlcNAcylation affects signaling pathways by cross-talk with kinases, modulates protein expression by cross-talk with the proteasome, and changes gene expression by altering protein-protein interactions, localization, and complex formation. The HBP and O-GlcNAc are recognized to mediate survival of cells in harsh conditions. Consequently, O-GlcNAc can affect many of the cellular processes that are relevant for cancer and is generally thought to be responsible for promoting tumor growth, disease progression, and immune escape. However, recent studies suggest a more nuanced view with O-GlcNAcylation acting as a tumor promoter or suppressor depending on the stage of disease or the genetic abnormalities, proliferative status, and state of the p53 axis in the cancer cell. Clinically relevant HBP and OGA inhibitors are already available and OGT inhibitors are in development to modulate O-GlcNAcylation as a potentially novel cancer treatment. Here recent studies that implicate O-GlcNAc in oncogenic properties of blood cancers are reviewed, focusing on chronic lymphocytic leukemia and effects on signal transduction and stress resistance in the cancer microenvironment. Therapeutic strategies for targeting the HBP and O-GlcNAcylation are also discussed.